2017
DOI: 10.1016/j.ijscr.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Conservative approach to Hepatic Portal Venous Gas: A case report

Abstract: HighlightsHepatic Portal Venous Gas (HPVG) is a rare condition often associated with a significant underlying pathologies.The mechanism underlying the passage of the gas from the intestine into the mesenteric, then portal, venous system is not fully understood.The high mortality rate made HPVG a cause of mandatory explorative laparotomy throughout the last fifty years of the twentieth century.The frequent presence of benign conditions underlying this condition has diverted the common therapeutic approach to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…Portal venous gas in combination with pneumatosis intestinalis might be a sign of intestinal ischemia but might also occur after blunt abdominal trauma or abdominal surgery [ 5 , 6 , 17 , 18 ]. In this patient, there was no evidence of intestinal ischemia from the clinical examination or the CT scan.…”
Section: Discussion Und Conclusionmentioning
confidence: 99%
“…Portal venous gas in combination with pneumatosis intestinalis might be a sign of intestinal ischemia but might also occur after blunt abdominal trauma or abdominal surgery [ 5 , 6 , 17 , 18 ]. In this patient, there was no evidence of intestinal ischemia from the clinical examination or the CT scan.…”
Section: Discussion Und Conclusionmentioning
confidence: 99%
“…HPVG in non-life-threatening cases, such as diverticulitis, gastric dilation and inflammatory bowel disease, has now been frequently diagnosed. Most of them are not dealt with surgical intervention, and unnecessary exploratory laparotomy is avoided [ 6 , 7 , 9 ]. One of the latest statistics showed the total in-hospital mortality was 27.3% [ 11 ], lower than the 39% reported by Kinoshita et al in 2001 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…By far the pathogenesis of HPVG remains unknown, and a number of hypotheses has been put forward [ 5 ]. HPVG has also been reported as a rare complication of surgical operations, such as endoscopic retrograde cholangiopancreatography (ERCP), liver transplantation, left colectomy, esophageal variceal band ligation and percutaneous endoscopic gastrostomy(PEG) [ 6 , 7 ]. Here we present a case of HPVG who underwent a transcathete cardiac defibrillator implantation via left subclavian vein with a comprehensive approach.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ginesu et al reported 1 case of HPVG in a patient who underwent a left colectomy for descending colon cancer; the patient was treated conservatively, and his symptoms resolved. [ 7 ] In addition, 2 cases of HPVG occurred during the course of chemotherapy in advanced colorectal cancer patients. [ 8 , 9 ] In our case, HPVG was found before the operation, and the patient was surgically cured.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 13 ] Case reports of HPVG associated with benign etiologies have increased with the wide use of CT, which might be one reason for the decrease in mortality of HPVG. [ 7 ] In addition, CT can predict the prognosis of HPVG. A recent study showed that outside of shock situations, HPVG involving 2 or fewer hepatic segments without pneumatosis intestinalis had a good predicted outcome.…”
Section: Discussionmentioning
confidence: 99%